The role of phonemes in shaping the structure of words: "An attempt to semanti-cally interpret the phenomenon of vowel alternation in Arabic morphology" - Muhammad, Al-Adawi Muhammad Radi (Al-Mukhtar Journal of Social Sciences, 2014)
Arabic grammarians used "Mīzān al-Ṣarf" to structure words. When encountering verbs with vowel letters, known as "al-Muʻtall," the assigned pattern didn't apply. They investigated the vowel's origin and found that hollow verbs could have a "wāw" or a "yāʼ" as the second letter in derived forms. This phenomenon, called "al-Iʻlāl" (vowel alternation), involved interchanging vowels and the glottal stop. It was classified into three categories: "al-Qalb" (interchanging), "al-Naqal" (transferring), and "al-Ḥaḍf" (omission).
Keywords: The morphological scale; the irregular verb; the origin of the vowel; the defects